Artichoke extracts: physiological effects, use in obstetric practice - О. В. Кравченко (Publishing House TRILIST, 2018)
The article has studied and analyzed numerous publications reflecting the results of studies on the physiological effects of artichoke extracts and the use of drugs on its basis in obstetric practice. The structural components of the artichoke are considered, the role of polyphenolic compounds, bioflavonoids, inulin, macro- and microelements in the biochemical processes of the organism is analyzed. Physiological effects of artichoke components were studied in detail. It is shown that they are not only antioxidant, but also hypocholesterolemic, membrane stabilizing, anti-inflammatory, antitumor, immunomodulating, etc. Artichokes have a great preventive potential for increasing the elimination functions of the liver and kidneys, a high antioxidant resource. The multicomponent composition of artichoke extracts determines the versatile effect of the preparations synthesized on their basis. An important feature of artichoke preparations is safety of use, the possibility of using without age restrictions, as well as in children and during pregnancy. The only contraindication for the appointment of an extracts of artichoke is the obstruction of the biliary tract. Particular attention is paid to the mechanisms of hepatoprotective and cholagogue effects of artichoke extracts. From the standpoint of evidence-based medicine, questions of the use of artichoke medications for gestosis, placental insufficiency, and conditions complicating the health of a pregnant woman are covered. In particular, the artichoke extract improves the state of chronic diseases of the gastrointestinal tract in pregnant women, reduces the severity of asthenic syndrome, improves fat metabolism, promotes the restoration of vitamin balance, protects the liver and kidneys from the effects of drugs used to relieve vomiting, increases the level of albumin, reduces bilirubin levels. In dermatosis of pregnant women, there is a decrease in cholestasis, elimination of itching. In jaundice in pregnant women artichoke extract provides hepatoprotective effect, reduces intrahepatic cholestasis, normalizes bilirubin levels in the blood. Since many diseases in pregnancy are accompanied by activation of lipid peroxidation, changes in the structural properties of cell membranes, metabolic disorders, the use of artichoke extracts is completely justified. Detoxication, antioxidant, lipidormalizing and hepatoprotective properties of preparations based on artichoke extracts indicate the high feasibility of their use in obstetric practice.